Sustainable catalysis, Part 1 - North, Michael, 1964-; Clark, James H. (Royal Society of Chemistry, 2015)
Catalysis is a fundamentally sustainable process which can be used to produce a wide range of chemicals and their intermediates. Focussing on those catalytic processes which offer the most sustainability, this two-part book explores recent developments in this field, as well as examining future challenges. Focussing on catalysis without metals or other endangered elements, each chapter covers a different type of organocatalyst. Beginning with chapters on acid and base catalysis, the book then concentrates on asymmetric catalysis. Several chapters cover pyrrolidine-based and cinchona alkaloid-based catalysts, whilst other chapters examine further organoctalysts which are constructed only from sustainable elements. Together with Sustainable Catalysis: With Non-endangered Metals, these books examine the progress in sustainable catalysis in all areas of chemistry, and are an important reference for researchers working in catalysis and green chemistry.
Title from publisher supplied information (Royal Society of Chemistry; title not viewed).
Keywords: Catalysis.; elektronické knihy; electronic books